A comparison of a level set method and the method of moving asymptotes for the topology optimization of flexible components in multibody systems. Issue 1 (24th March 2023) - Azari Nejat, Ali; Held, Alexander; Seifried, Robert
Abstract: The gradient‐based topology optimization of flexible multibody systems is considered, where the floating frame of reference method is utilized to model the flexible components with an appropriate efficiency. Thereby, the quality of the optimization results depends, among others, on the chosen gradient calculation strategy and the applied optimization algorithm. Here, both a fully‐coupled time‐continuous adjoint sensitivity analysis and a weakly‐coupled equivalent static load method are tested for gradient calculation. Moreover, both the method of moving asymptotes and a level set method are taken to solve the optimization problem. Different combinations of the mentioned gradient strategies and optimization algorithms are applied for the topology optimization of a flexible piston rod in a slider‐crank mechanism. The corresponding results and comparisons shall be used as quality benchmarks for further studies.